Particle Size and Hydration Properties of Dried Apple Pomace : Effect on Dough Viscoelasticity and Quality of Sugar-Snap Cookies - Rocha Parra, Andrés Felipe (2019)
Apple pomace (AP) is a by-product of the juice industry, rich in dietary fiber (45.06%), which is generated in large quantities. The objectives of the present work were to evaluate the effect of the particle size and the level of replacement with AP on the quality of sugar-snap cookies. Dehydrated AP was ground to three different particle sizes (d(4,3) = 362, 482, 840 μm) to substitute 15% and 30% of wheat flour in cookie formulations. The quality of dough and cookies was evaluated in terms of rheological properties, color, texture, and global acceptability of the final product. When the AP particle size decreased, the water absorption properties (WHC, WBC) were higher (33 and 10% respectively for the lowest and the highest particle size). For both replacement levels, the smallest particle size (362 μm) led to the highest dynamic moduli of dough. The spread ratio (SR) of the cookies diminished when the particle size decreased (from 6.4 to 4.8 corresponding to AP840 and AP362 respectively). The lowest SRs were obtained for the 30% replacement level except for AP362. When employing AP with the largest particle size (840 μm), the cookies were less hard (48.7 N). The addition of AP to sugar-snap cookies led to higher global acceptability scores than for control cookies. The sensory attribute that most differentiated the cookies with AP was their pleasant taste being the taste score always higher than the control one.